The Effect of Turkish-Muslim Congresses on the Bolshevik Revolution in Tsarist and Bolshevik Russia Period - Ahmet Karaca (Avrasya İncelemeleri Dergisi)
The end of the 19th Century witnessed Turkestan’s occupation by Tsarist Russia. This occupation started with the capture of Kazan by Ivan the Terrible in 1552; it was followed by the conquest of the Khanates of Siberia, Astrakhan, and Crimea, concluding with the capture of the Kazakh Hordes, Hive, Hokand, Bukhara, and Turkmen settlements. While the occupation continued, Russia began implementing a policy characterized by rapid assimilation at the political and cultural levels in Turkestan. The administration was seized from the Khans and transferred to the Russian rulers. However, by 1905, Russia began to implode. Some national and political movements ensued under the leadership of the Kazan Tatars. Yusuf Akçura, Abdürreşit Ibrahim and Ismail Gaspıralı’s contributions to these movements were noteworthy. By 1905, the Turks of Russia had begun aligning their political activities with the attainment of freedom, holding several congresses from 1905 to 1917.